Effect of Pruning and Thinning on Growth, Yield and Quality of Pomegranate - Pawar, S K; Desai, U T; Choudhari, S M (Annals of Arid Zone, 2016)
Shoot length and number of leaves per shoot increased with the pruning intensity. Pruning also delayed the bud sprouting, flower appearance and harvesting. Although, the highest yield was obtained from unpruned trees, the 40 cm pruning of main stems was comparable with it. . The number and percentage of better grade fruits were more in higher severity of pruning. The fruit size, juice content and TSS were better with increasing severity of"pruning. The rind and aril colour, aril content and seed hardness were not appreciably influenced by pruning treatments.